Las técnicas de gamificación y su incidencia en el desarrollo de habilidades cognitivas en los niños y niñas de 4 a 5 años en el nivel de educación inicial de la escuela de educación básica “Isabel Herrera de Velázquez” durante el periodo lectivo 2019- 2020 - Liberio Ambuisaca, Xiomara Paola (2019)
This paper aims to verify how gamification techniques, through play, develop cognitive skills, which can develop recreational or gamification-based methodologies, as a way of contributing, improving motivation, effort and active student participation. at the level of education, at the same time, that allow students to stimulate learning by promoting their cognitive abilities, that is, learn to learn. The advancement of technology drives major changes in education, challenging the methodology of the teaching-learning process, with new objectives and the use of easy-to-use technological tools, through technological means, in which both the teacher and The student learns in a practical way and by discovery since children are born in the technological age and do not make them unknown until they become familiar with these tools for the development of cognitive skills. Therefore, this project on gamification techniques aims to verify how students from the initial level respond to the implementation of didactic proposals based on gamification techniques to be able to take into account the use of these resources in this educational level, without leaving sideways the initial education curriculum where its methodology is based on the game and the experiences.